Undergraduate student experience of COVID-19 anxiety: opinions, dysfunctional beliefs, and anxiety symptoms - Byam, Layton (My University, 2021)
The COVID-19 pandemic is an international health crisis that has changed the experience of undergraduate students across Canada. As of February 23rd, 2021, Canadian officials have reported over 800 thousand cases and 21 thousand deaths due to COVID-19. Additionally, there has been a rise in anxiety reported throughout the general population. The current study aims to examine the links between anxiety disorder symptoms, anxiety-related dysfunctional beliefs, and COVID-19-related anxiety in an undergraduate sample. Additionally, the study seeks to examine how COVID-19 anxiety, anxiety disorder symptoms, and anxiety-related dysfunctional beliefs are related to undergraduate students' opinions of their current school circumstances and pandemic experience. To measure students' COVID-19 anxiety, participants completed the Coronavirus 19 Phobia Scale, the Fear of Coronavirus Scale, and the COVID Stress Scales. Participants also completed online measures of health anxiety, generalized anxiety disorder, panic disorder, social anxiety disorder, and obsessive-compulsive disorder symptoms. To measure participants' anxiety-related dysfunctional beliefs, scales were completed to measure anxiety sensitivity, intolerance of uncertainty, metacognitions, disgust propensity and sensitivity, somatosensory amplification, and body vigilance. The investigated opinions included attitudes towards in-person classes, campus life, conspiratorial beliefs, and their anticipated physical response to potentially contracting COVID-19. Additionally, participants reported the perceived risk to themselves and those around them if they contracted the virus. Data was collected from a total of 593 MacEwan students between September 2020 and January 2021. Preliminary findings will be presented at Student Research Day.
Presented on April 26, 2021 at Student Research Day held virtually at MacEwan University in Edmonton, Alberta.
Keywords: anxiety; COVID-19